2017
DOI: 10.1002/2016wr019426
|View full text |Cite
|
Sign up to set email alerts
|

PeaksOverThreshold (POT): A methodology for automatic threshold estimation using goodness of fitp‐value

Abstract: Threshold estimation in the Peaks Over Threshold (POT) method and the impact of the estimation method on the calculation of high return period quantiles and their uncertainty (or confidence intervals) are issues that are still unresolved. In the past, methods based on goodness of fit tests and EDF‐statistics have yielded satisfactory results, but their use has not yet been systematized. This paper proposes a methodology for automatic threshold estimation, based on the Anderson‐Darling EDF‐statistic and goodnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 30 publications
1
48
0
1
Order By: Relevance
“…In general, a P value can be seen as a continuous measure of the compatibility of the data with the entire model (Greenland et al, ), but as far as we know, no theoretical argument has been provided to show that MAXPV will lead to better estimates, and its empirical behaviour has been studied in a limited number of situations (Solari et al, ). Because the P values p i are computed from nested samples (except perhaps some differences due to declustering), they are likely autocorrelated.…”
Section: Methodsologymentioning
confidence: 99%
See 1 more Smart Citation
“…In general, a P value can be seen as a continuous measure of the compatibility of the data with the entire model (Greenland et al, ), but as far as we know, no theoretical argument has been provided to show that MAXPV will lead to better estimates, and its empirical behaviour has been studied in a limited number of situations (Solari et al, ). Because the P values p i are computed from nested samples (except perhaps some differences due to declustering), they are likely autocorrelated.…”
Section: Methodsologymentioning
confidence: 99%
“…Examples of such application were presented by Choulakian and Stephens (2001) on Canadian rivers and by Li, Cai, and Campbell (2005) on extreme precipitation in South-West Australia. However, according to Solari, Egüen, Polo, and Losada (2017), the range of valid thresholds derived from this strategy can be larger than what is practically acceptable, which motivated them to investigate the selection of thresholds associated with the highest P value. Their study showed that, in some situations, their approach led to higher and more relevant thresholds.…”
Section: Introductionmentioning
confidence: 99%
“…First, the interpretation of these plots is unclear in practice [17], and it is clearly difficult to determine which portion of the curve is completely linear. Second, graphical techniques cannot be automated and the uncertainty associated with threshold selection cannot be estimated [55]. Figure 2 shows a range of potential optimum threshold values, making the use of a single value from the range in the analysis subjective.…”
Section: Threshold Selection Methodsmentioning
confidence: 99%
“…An indicator for determining if a threshold was correctly selected is to use a goodness-of-fit test to verify that GPA is a proper 120 distribution (Davison and Smith, 1990). The p-value of such tests were used recently to develop automatic selection procedures based on the identification of the maximum p-value and the first threshold respecting a given significance level (Durocher et al, 2018b;Solari et al, 2017).…”
Section: Regions 105mentioning
confidence: 99%